A review of the tectonic and metamorphic history of the region around Lutzow-Holmbunta, East Antarctica (abstract) - Yoshida, Masaru; Suzuki, Morihisa; Shirahata, Hiroshi; Kojima, Hideyasu; Kizaki, Koshiro (1983)
P(論文) Recent studies of the tectonic-metamorphic history of the Lutzow-Holmbukta region are critically reviewed and summarized as follows. First event (ca. 1900 Ma ago) is the high-pressure granulite facies metamorphism with recumbent and isoclinal folds. Second event (ca. 1100Ma ago) is the intermediate pressure granulite facies metamorphism and charnockite formation probably associated with some folding tectionics. Third event (ca. 560Ma ago or earlier) is the high amphibolite facies metamorphism associated with E-W upright foldings. Fourth event (ca. 460Ma ago) is the low amphibolite facies metamorphism associated with N-S upright folds and faults and pink granite intrusion, succeeded by the greenschist facies or slightly lower grade metamorphism. Fifth event (Jurassic?) is the fracturing under stress field with N-S maximum extensional axis. Some problems and alternative explanations are briefly discussed with conclusions that there remain some problems on the preferred metamorphic-tectonic history. departmental bulletin paper